PSVI-20 Impact of Saccharomyces cerevisiae fermentation products on in vitro rumen microbial fermentation of new crop corn silage - Reedy, Coleman G (J Anim Sci, 2020)
Dairy cows fed silage towards the front edge of a bunker have shown decreased performance often referred to as the new crop corn silage slump. The objective of this study was to evaluate the effect of Saccharomyces cerevisiae fermentation product, NutriTek® (NutriTek), on in vitro volatile fatty acid (VFA) production using new crop corn silage collected at various distances from the front edge of the bunker as substrate. Silage was sampled at 1.8, 3.6 and 7.2 m from the front edge of the bunker by taking the entire face of the silage and mixing. NutriTek was added to each serum bottle relative to the recommended feeding rate of 19 g/d along with 0.3 g of silage as substrate. Each serum bottle was inoculated with 40 mL of buffered rumen fluid from cows on a diet consisting of 70% forage and 30% concentrate and was incubated for 24 h. Ten replicates were run per treatment. After incubation, VFA production was measured. Data were analyzed using the GLM model of JMP. Means were compared using Tukey test and significance was defined as P < 0.05. There was a linear trend of decreasing silage pH as sample depth increased; 4.01 at 1.8 m, 3.71 at 3.6 m, and 3.56 at 7.2 m. Results showed that VFA production was reduced for 1.8 m sample compared to the 3.6 m and 7.2 m samples (Table 1). NutriTek was able to improve acetate, propionate, and total VFA production over Control at all corn silages tested (Table 2). In addition, NutriTek showed the ability to elevate VFA production of the 1.8 m sample to Control samples at 3.6 and 7.2 m. In conclusion, NutriTek could be a management tool to address the performance slump of dairy cows when transitioning to a new crop corn silage. [Image: see text]